贡嘎山海螺沟冰川沉积的石英砂扫描电镜形态特征分析 - 石磊; 张跃; 陈艺鑫; 傅海荣; 刘耕年 (北京大学学报 自然科学版, 2010)
对贡嘎山海螺沟冰川沉积物中石英砂进行扫描电镜形态特征分析,获得海洋性山岳冰川沉积的标志性形态特征如下: 尖锐的棱角状颗粒形态占绝对优势,边棱尖锐、表面起伏度高;大型-中型贝壳状断口极发育,多见平行解理面、阶梯状断口;具有标志冰川磨蚀作用的擦痕、新月形凿口和压裂深坑;有明显的化学溶蚀和沉淀形态,如溶蚀坑、溶蚀沟,硅质薄膜、硅质球和黏土矿物.结果表明海螺沟冰川具有强烈的侵蚀作用,机械压碎、研磨在侵蚀和搬运过程具有绝对优势;同时海螺沟冰川底部存在丰富的冰下融水,起到化学溶蚀和沉淀的作用.石英砂表面结构统计分析结果与河流、湖泊、海岸、风沙等沉积明显不同,与青藏高原、南极等地大陆性冰川沉积分析结果亦存在差异. The SEM microtextures of glacial sediments samples taken from Hailuogou Glacier are analyzed. The major microtextures are listed as follows: sharp angular features with sharp edges and high relief;large-medium conchoidal fractures, parallel cleavage and terraced fractures, indicating mechanical fragmentation;stria, crescentic gouges and crushed deep hole, indicating abrasion;dissolution pits and grooves, siliceous sphere and clay minerals, indicating chemical dissolution and precipitation. These results indicate that there are intensive erosion processes and chemical dissolution processes under Hailuogou Glacier. The statistical analyses show that the quartz grain SEM microtextures of maritime glacial deposits are different from that of fluvial, lacustrine, coastal and eolian deposits, as well as that of continental glacial deposits in Antarctic and inside Tibetan Plateau. 国家自然科学基金; 高等学校博士学科点专项科研基金 中文核心期刊要目总览(PKU) 中国科技核心期刊(ISTIC) 中国科学引文数据库(CSCD) 0 1 96-102 46